2012
DOI: 10.1055/s-0032-1314828
|View full text |Cite
|
Sign up to set email alerts
|

Abgleich von Sekundärdaten mit einem epidemiologischen Krebsregister auf der Basis verschlüsselter Personendaten - Ergebnisse einer Pilotstudie in Nordrhein-Westfalen

Abstract: The DMP-DM2 records were encrypted and linked to cancer registry data with a moderate personnel and financial input and high efficiency. Linked records were instantly usable for epidemiological analyses. Experiences of the pilot study suggest that future linkage studies can further advance the level of data protection, without losses in efficiency, by moderately complex software modifications and amendments of the data flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
0
7
0
2
Order By: Relevance
“…Cancer cases of this cohort were assessed by the federal cancer registry of NRW. The cancer registry performed a pseudonymized record linkage by using encrypted personal identifiers instead of plaintext data ( 19 , 20 ). Additionally, issues arising from name changes were addressed by utilizing information on common changes from previous studies on ethnic German migrants.…”
Section: Methodsmentioning
confidence: 99%
“…Cancer cases of this cohort were assessed by the federal cancer registry of NRW. The cancer registry performed a pseudonymized record linkage by using encrypted personal identifiers instead of plaintext data ( 19 , 20 ). Additionally, issues arising from name changes were addressed by utilizing information on common changes from previous studies on ethnic German migrants.…”
Section: Methodsmentioning
confidence: 99%
“…in admission and discharge dates), reflecting an ad hoc deterministic linkage. In contrast to the recently published use of linkage procedures based on encrypted personal identifiers or use of a probabilistic record linkage [15,16], an extensive hand search of both anonymous data sets might have offered the possibility of isolating patients’ data that were mistakenly omitted from one registry and/or to answer the question of how many persons were missed by our linkage criteria. Because of the huge efforts in time and resources, we waived a thorough hand search.…”
Section: Discussionmentioning
confidence: 99%
“…The analyses were limited to invasive breast cancer diagnoses among women (ICD-10: C50). The cancer diagnoses of resettlers from the AMIN study were identified in the federal cancer registry of NRW using a pseudonymised record-linkage procedure [23,24]. In addition to the resettler status, the dataset contained information about the age at diagnosis, date of diagnosis and TNM status (T: tumour size, N: lymph node involvement, M: metastases).…”
Section: Variablesmentioning
confidence: 99%